Design of a motion capture trial for upper limb movement analysis - Yamini Bhaskar (2013)
Stroke rehabilitation is a major area of research in today’s world, in particular motion tracking. In order to monitor a patient’s progress in rehabilitation, an efficient motion tracking system needs to be in place in a hospital, taking into mind, space limitations. This thesis aims to provide an optimal system to track the upper limb movement of normal subjects and address any issues that may arise due to motion tracking, such as occlusion of markers, to provide a stable and reliable system for future trials to be conducted on stroke patients in hospitals. A total of 18 healthy subjects were asked to perform 9 activities of daily living and their movements were tracked by the Qualysis motion capture system. Issues such as occlusion which is bound to occur in any motion tracking system, were minimized by the creation of rigid bodies. The limitations and merits of the system are highlighted, with potential suggestions and future applications of this system.